Community structure and regeneration pattern of Abies spectabilis in Sagarmatha National Park, Central Himalaya, Nepal - Nagarkoti, A. B.; Pathak, M. L.; Pandey, B.; Devkota, A. (Banko Janakari, 2019)
Community structure and regeneration pattern of Abies spectabilis was studied along the elevation gradient from 2750 to 3550 m asl in mixed forest of A. spectabilisin Sagarmatha National Park, eastern Nepal. Various community attributes (viz. importance percentage, species diversity and beta diversity) and population characteristics (e. g. density- diameter, bar diagram) were analysed. Out of the thirty four species recorded from the study forest, A. spectabilis was the co-dominant species with high species diversity. Total tree density was the highest at 3450 m and the lowest at 3550 m. Elevation appeared to be the important environmental factor that affects the community attributes of the study forest. The curve for A . spectabilis solely was lightly deviated from the typical reverse J-shaped which indicates a discontinuous regeneration pattern. The distribution of the seedling and sapling distribution was not uniform. Seedling mortality was found relatively medium and development of seedlings into saplings was also low. The lower number of sapling might be due to moderate disturbance (grazing and trampling) by livestock or due to environmental factors. The use of Abies tree for construction and firewood might be the reason of un sustainability.